Sputter deposited hydroxyapatite thin films to enhance osseointegration - Riedel, Nicholas Alfred, author; Williams, John D., advisor; Popat, Ketul, advisor; Prieto, Amy L. (Amy Lucia), committee member (Colorado State University. Libraries, 2010)
As the demand for hip and knee replacements continues to grow, researchers look to increase the operational lifetimes of these implants. Many of these implants fail as a result of aseptic loosening caused from repeated loading of these joints. It is thought that implant life could be extended by improving the interface between the implant and natural tissue. To this effect, hydroxyapatite coatings have been demonstrated to improve implant to bone bonding and allow a more natural integration of the metallic substrates. This work explores the potential of using ion beam etching and sputter deposition to produce a hydroxyapatite thin film with a unique surface topography that would potentially enhance osseointegration. First, the effects of ion etching bare titanium were evaluated. Three ion energies (300 eV, 700 eV, and 1100 eV) were used to etch either as-received or polished substrates. Topographical changes were examined by scanning electron microscopy. Rat mesenchymal stem cells were differentiated to osteoblasts to test the biocompatibility of the surfaces with bone cells. It was found that ion etching the titanium increases cellular activity, and an ion energy of 700 eV appears to create the most beneficial topography. Hydroxyapatite thin films were then sputter deposited on titanium substrates etched at 700 eV. After the coatings were deposited, some of the hydroxyapatite films were re-etched in efforts to induce a unique topography. It was found that the hydroxyapatite coatings improved short term cell response but degraded over the course of the culture. Further investigation showed the as-sputtered coatings were amorphous. To prevent degradation of the coatings, annealed films were then prepared by heat treating at 600 °C for 2 hours. X-ray diffraction was used to confirm the presence of a crystalline hydroxyapatite phase. Films were immersed in culture media for four weeks, showing no signs of degradation. Ion etching performed on the substrates post annealing yielded a unique topography in the hydroxyapatite film. A final study was conducted evaluating the MSC response to the annealed and post-anneal etched films. It was found that the post-anneal etched hydroxyapatite coating had the highest cellular activity, indicating that this preparation may be an effective means to enhance osseointegration on medical implants.
Department Head: Allan Thomson Kirkpatrick.